MURAL DI LINGKUNGAN SEKOLAH DALAM KONTEKS PENDIDIKAN KONSERVASI - Suherman Suherman; Sunarto Giyanti; Sri Prastiti Kusuma Anggraeni (Universitas Muria Kudus, 2019)
The task of education in general is to deliver, to create quality individuals or learners, to be noble in character, and to be dedicated to the nation and people. In the world of formal education, it is known as conservation education, namely education programs that instill and preserve socio-cultural values (justice) which are considered as guidelines for humans as individuals who live in a social group. Conservation education in its latest development is no longer only done in the classroom orally and in writing, but the visual learning model outside the classroom has also been practiced. Mural in the context of conservation education in schools has an active role as a medium of learning with visual methods to improve students' understanding and knowledge of socio-cultural values.